Alcohol and marijuana use in early adulthood for at-risk men: Time-varying associations with peer and partner substance use - Washburn, Isaac J. (2014)
BACKGROUND: Time-varying associations of 185 at-risk men’s (from the Oregon Youth Study) substance use with that of their peers and partner over a 10-year period (ages 23 to 32 years) were examined. Moderation of effects by time with peers and partner and their age were tested. METHOD: Growth models were used to predict changes in heavy episodic drinking (HED) alcohol use and marijuana use as a function of substance use by their female partners and male peers. RESULTS: Time with peers and peer substance use significantly predicted HED (ORs=1.6, 2.3), alcohol use (ORs=1.6, 2.1), volume of alcohol use (IRRs = 1.5, 1.3), and marijuana use (ORs=12.8, 1.7); peer marijuana use predicted volume of marijuana use (B=2.5). Partner substance use significantly predicated marijuana volume (B=2.7). Partner alcohol use predicted alcohol volume (IRR=1.1), but was moderated by time with partner and age (IRR=1.0). Time with partner and partner marijuana use predicted marijuana use (OR=0.5, 2.7), as did the interaction of the two (OR=3.8). CONCLUSIONS: Outcome-specific substance use of peers and partners was significantly associated with indicators of alcohol and marijuana use in men’s early adulthood, with robust effects of peer substance use through age 30 years and with time spent with peers influencing alcohol use. Time with partner was protective against marijuana use unless the partner used marijuana. Peers and partners should be considered in intervention efforts to effectively reduce men’s substance use in early adulthood.